Nowsze badania nad I wojną światową w Europie Środkowo-Wschodniej i Południowo-Wschodniej (wybrane zagadnienia) - Borodziej, Włodzimierz; Górny, Maciej (Kwartalnik Historyczny, 2015)
Recent Studies about the First World War in Central-Eastern and South-Eastern Europe (Select Problems) The article discusses chiefly the main trends of research pursued in the past few years and dealing with the Eastern and South-Eastern theatre of the First World War. The most essential new trend seems the cultural turn. One of its consequences is researchers’ rising interest in Central-Eastern Europe and the Balkans, followed by a comprehensive analysis of a number of aspects of the phenomenon of violence. The authors include in the latter the occupation experienced by the Eastern and Balkan theatres to an extent much greater than in the case of the remaining regions. A successive aspect involves forced migrations of the civilian population – refugees and victims of deportations. Violence is also associated with the situation of prisoners of war, more numerous along the Eastern Front than the Western one. Most of those phenomena occurred and even progressed also after the end of World War I, and did not finish until the first half of the 1920s. This is true in particular for anti-Jewish pogroms and armed conflicts accompanying the delineation of the frontiers of the new states in the region. A survey of studies ends with a presentation of the as yet scarce symptoms of commemorating the Great War in Central-Eastern and South-Eastern Europe.